On the determination of optimal designs for an interference model - Joachim Kunert; R. J. Martin (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2000)
This paper generalizes Kushner's (1997) method for finding optimal repeated measurements designs to optimal designs under an interference model. The model we assume is for a onedimensional layout without guard plots and with different left and right neighbour effects. The resulting optimal designs may need many blocks or may not even exist as a finite design. The results give lower bounds for optimality criteria on finite designs, and the design structure can be used to suggest efficient small designs.
Keywords: 519; Interference model; Neighbour effect; Optimal design; Universal optimality